Tumor Cells and Tumor-Associated Macrophages: Secreted Proteins as Potential Targets for Therapy. (17th November 2011) - Baay, Marc; Brouwer, Anja; Pauwels, Patrick; Peeters, Marc; Lardon, Filip
Abstract : Inflammatory pathways, meant to defend the organism against infection and injury, as a byproduct, can promote an environment which favors tumor growth and metastasis. Tumor-associated macrophages (TAMs), which constitute a significant part of the tumor-infiltrating immune cells, have been linked to the growth, angiogenesis, and metastasis of a variety of cancers, most likely through polarization of TAMs to the M2 (alternative) phenotype. The interaction between tumor cells and macrophages provides opportunities for therapy. This paper will discuss secreted proteins as targets for intervention.